A planning model for petroleum refineries - Pinto,J.M. (2000)
The main objective of this paper is to develop a nonlinear planning model for refinery production. The model described here represents a general petroleum refinery and its framework allows the implementation of nonlinear process models as well as blending relations. This model assumes the existence of several processing units, producing a variety of intermediate streams, with different properties, that can be blended to constitute the desired kinds of products. Two real-world applications are developed, one for the planning of diesel production in the RPBC refinery in Cubatão (SP) and the other for the general production planning in the REVAP refinery in S. José dos Campos (SP). In both cases, different market scenarios were analyzed using the planning optimization and the results were compared with the current situation, in which there is no extensive use of planning decision support tools. Results revealed that there is a very large potential of profitability embedded in the planning activity, reaching several millions of dollars per year.